1998
DOI: 10.1006/viro.1997.8986
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a Carboxy-Terminal Region of Vesicular Stomatitis Virus Glycoprotein G That Affect Membrane Fusion Activity

Abstract: The envelope glycoprotein G of vesicular stomatitis virus induces membrane fusion at acidic pH. A highly conserved amino terminal region spanning residues 123 to 137 has previously been identified as an internal fusion domain. Here we have substituted specific amino acids within a carboxy terminal region, conserved in five vesiculoviruses encompassing residues 395 to 418, and studied the effect of these mutations on membrane fusion at acid pH and pH-dependent conformational change. Substitution of conserved Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 69 publications
2
31
0
Order By: Relevance
“…(b) Region of the glycoprotein of VSV and RV involved in the control of the pH-dependent structural changes leading to fusion aligned with the equivalent region of VHSV. * Positions of mutations which affect the fusion process of VSV (Shokralla et al, 1998) ; † positions of mutations of the RV glycoprotein which affect the structural transitions of RV G (Gaudin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) Region of the glycoprotein of VSV and RV involved in the control of the pH-dependent structural changes leading to fusion aligned with the equivalent region of VHSV. * Positions of mutations which affect the fusion process of VSV (Shokralla et al, 1998) ; † positions of mutations of the RV glycoprotein which affect the structural transitions of RV G (Gaudin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…5 b). Mutations in this latter region have been shown to affect the fusion properties of RV and VSV G proteins (Gaudin et al, 1996 ;Shokralla et al, 1998), possibly by influencing the low-pH-induced conformational changes necessary for fusion activity. Our finding that (i) mutations at position 140 were always associated with a concomitant change at position 431 or 433 and that (ii) we could not select a revertant with a single mutation at this position, provided the first concrete argument that regions I and II are structurally linked in the native G protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another region of G protein, encompassing residues 395 to 418 for VSV or containing residues 392 to 396 for rabies virus, has been identified as a segment that affects the fusogenic activity of the protein by influencing the low-pH-induced conformational changes (45,51). In addition, it has also been shown that not only the ectodomain segment but also the membrane anchoring domain is required for VSV fusion activity (52,53).…”
Section: Determination Of the Rhabdovirus Fusion Peptidementioning
confidence: 99%
“…However, other studies demonstrated that amino acids 395-418 (the membrane-proximal region) have an significant influence on fusion (25), and additional studies identified region 145-164, termed the p2-like peptide, as being a pivotal domain in facilitating glycoprotein G-mediated membrane fusion (26,27). A synthetic p2 peptide was shown to mediate liposome-liposome fusion in a low pHand phosphatidylserine-dependent manner (27).…”
mentioning
confidence: 99%